Purification and characterization of a thermostable phycoerythrin from hot spring cyanobacterium leptolyngbya sp. KC45 - Chayakorn Pumas (2018)
This study aimed to understand characteristics of thermostable phycoerythrin from hot spring cyanobacteria Leptolyngbya sp. KC45. Phycoerythrin was purified with the purification index at 17.38 of A565/A280 ratio and demonstrated as two protein bands of 21 and 18 kDa under SDS-PAGE analysis. The native protein was assumed to be hexamer with a molecular mass of approximately 235 kDa based on the results from gel filtration. N-terminal amino acid sequences shared the highest percent of identities with Fremyella diplosiphon Fd33 at 100% and 90% for α- and β-subunit, respectively. Phycoerythrin and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity remained at approximately 80% of the original level after being heated at 60°C for 30 min, indicating that it can be considered as the promising thermostable phycoerythrin. © 2012 Friends Science Publishers.